La infección urinaria recurrente en urología: Pautas diagnósticas y terapéuticas. - Corral Rosillo, J.; Delgado Martín, J.A.; Moreno Sierra, Jesús; Resel, Luis; Gómez Vegas, Ángel; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1997)
Sin resumen